2012
DOI: 10.1128/jvi.00047-12
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Infectious Salmon Anemia Virus Receptor on Atlantic Salmon Endothelial Cells Correlates with the Cell Tropism of the Virus

Abstract: Infectious salmon anemia (ISA) is a World Organization for Animal Health (OIE)-listed disease of farmed Atlantic salmon, characterized by slowly developing anemia and circulatory disturbances. The disease is caused by ISA virus (ISAV) in the Orthomyxoviridae family; hence, it is related to influenza. Here we explore the pathogenesis of ISA by focusing on virus tropism, receptor tissue distribution, and pathological changes in experimentally and naturally infected Atlantic salmon. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
148
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(166 citation statements)
references
References 51 publications
18
148
0
Order By: Relevance
“…the functional shift of cell and organ tropism from an epithelial to an endothelial infection, including generalized dissemination. This is in agreement with our previous findings that non-virulent ISAV-HPR0 causes only a localized epithelial infection of mucosal surfaces of the gills and skin [19,49], whereas virulent ISAV-HPR-deleted shows a generalized endothelial infection of the circulatory system [50]. Furthermore, recent functional analysis demonstrated that deletions in the HE-HPR promote ISAV receptor fusion of viral and cellular membranes by which the virus delivers its genetic material into the host cell for subsequent replication [23].…”
Section: Discussionsupporting
confidence: 81%
“…the functional shift of cell and organ tropism from an epithelial to an endothelial infection, including generalized dissemination. This is in agreement with our previous findings that non-virulent ISAV-HPR0 causes only a localized epithelial infection of mucosal surfaces of the gills and skin [19,49], whereas virulent ISAV-HPR-deleted shows a generalized endothelial infection of the circulatory system [50]. Furthermore, recent functional analysis demonstrated that deletions in the HE-HPR promote ISAV receptor fusion of viral and cellular membranes by which the virus delivers its genetic material into the host cell for subsequent replication [23].…”
Section: Discussionsupporting
confidence: 81%
“…This finding demonstrated that the ILT responded to systemic infection in a distinct manner compared with the other tissues examined, especially noteworthy the gills, in which the ILT is embedded. Previous investigations have shown the presence of the ISAV cellular receptor in the ILT by IHC (28), whereas the absence of replicating ISAV has been shown by a RT-qPCR assay (4). These findings indicate that the changes observed in the ILT most likely are consequences of a systemic and not a local response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated ISAV receptor expression on gill mucosal epithelial cells [33] and high prevalences of ISAV positive gills by RT-PCR [31,34], suggesting ISAV infection of gill cells. However, such infections have not been confirmed at the cellular level.…”
Section: Resultsmentioning
confidence: 99%
“…As they filter large amounts of water they offer a suitable target for invading infectious agents. While RT-PCR detection of ISAV on whole gill preparations has suggested the gills as an entry-site for ISAV infection [31], in vivo studies have only reported ISAV infection within endothelial cells and leucocytes [11,32,33]. We showed previously that gill and hind-gut mucosal epithelial cells express the ISAV 4- O- acetylated sialic acid receptor on the cell surface [33], indicating the potential for ISAV-infection of epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation